ANALISIS STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) DALAM PENYAJIAN LAPORAN KEUANGAN PADA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) (STUDI KASUS PADA UMKM PANDAI BESI DI DESA PALAHIDU BARAT KEC. BINONGKO) - Malik, Ernawati; Ninni, Wa (JIEM : Journal Of International Entrepreneurship And Management, 2024)
This study aims to determine the financial accounting standards carried out by Blacksmith MSMEs in West Palahidu Village, Binongko District, and the compatibility between financial accounting standards in West Palahidu Village, Binongko District, and SAK ETAP. The research method used is qualitative descriptive analysis. This research was conducted at the Blacksmith MSME in Palahidu Barat Village, Binongko District, located in Southeast Sulawesi Province. The study will be conducted in April-May 2023. The results showed that the accounting information system carried out by Blacksmith MSMEs was still very simple and the recording process was still carried out manually (filing notes). And it is stated that it is not in accordance with SAK ETAP because it does not record financial statements and does not have types in financial statements, namely profit / loss statements, statements of changes in equity, balance sheet statements, cash flow statements and notes to financial statements. This is due to the inability or lack of information in recording financial information